Digitalization of utilities meter and mesh networking applications - Lim, Pui Shan (2021)
This project is a Digitalization and Mesh Networking design project. It will provide a Smart Grid system with the concept of Digitalization and Mesh Networking. The traditional meter system might be inefficiency and ineffectiveness in term of resources needed, accuracy and time consumption. The reason is because traditional meter system need human intervention to the process of collecting data of utilities used, that might cause errors or faults due to error reading and error inserted of the meter reading data. Besides, traditional meter system need a huge number of manpower as a meter reader who need to travel a lot to collect the meter reading from house to house. The financial requirement for the manpower and also the transportation fees is a heavy burden for the utility suppliers. Also, the process of collecting data by human intervention is a time consuming process due to the needs of physically access and reading of the utilities consumption data. Therefore, the Smart Meter system is designed to provide a system solution that can help to improve the efficiency and effectiveness in the whole progress of collecting and transmitting the meter reading data. This system will need to install a Pi camera in front of the utilities meter. This Pi camera will trigger the command to capture the image of the meter reading when the predefined timer is reached. Then, the system will need to implement the OCR image processing technique in Python3 by using Opencv and tesseract libraries. This is to achieve the digitalization of utilities meter, so that the utilities consumption data in digital form can be retrieved from the image captured by the Pi camera. After that, the system will transmit the data by implementing the technique of mesh networking in the Raspberry Pi 3B+. The data retrieved from the image will be transmit through the mesh network hop by hop and finally it will be uploaded to the cloud for further calculation purpose by the utility companies or suppliers. In a nutshell, this project will come out with a smart utilities system that is suitable for the utilities company to improve or migrate from current traditional system to a smart system.